Social capital and job search assistance: A multilevel analysis of East Asian countries - Kim, Harris Hyun-soo (International Sociology)
This study analyzes the network antecedents of receiving job search assistance, specifically how and to what extent social capital relates to this process. Data come from probability samples on four East Asian countries. Hierarchical linear models are estimated to investigate the associations between social capital and inequality in the receipt of information and influence from personal contacts during job search. Adjusting for confounders, organizational affiliation, civic participation, and frequency of social interaction significantly predict the rate of assistance. Also significant are network size and diversity. Net of compositional effects, regional-level civic participation is further associated with the outcome. Finally, three significant cross-level interactions are observed with respect to social network characteristics (size and diversity). Understanding why some people receive more job search assistance is fundamental to status attainment and labor market inequality. Findings herein shed new light on this critical, yet underexplored, issue. - Reproduced.
Keywords: Social capital; Employment creation